1998
DOI: 10.2165/00002018-199819060-00005
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Neuropathy with Nucleoside Antiretrovirals

Abstract: Distal symmetrical peripheral neuropathy is a common adverse experience in persons with HIV infection. This condition, which presents as a pain, numbness. burning and/or dysaethesia initially in the feet, is often multi-factorial in its origin. Nucleoside analogue reverse transcriptase inhibitors represent an important contributor to peripheral neuropathy. Specifically, around 10% of patients receiving stavudine or zalcitabine and 1 to 2% of didanosine recipients may have to discontinue therapy with these agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
111
0
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(123 citation statements)
references
References 41 publications
8
111
0
4
Order By: Relevance
“…After treatment with antiretroviral drugs, 10-30% of patients report signs of drug-associated peripheral neuropathies, such as a bilateral pain and burning dysesthesia in the lower extremities [49,37,35,36]. In a non-randomized clinical trial, Famularo and colleagues reported that HIV patients with lower levels of L-acetylcarnitine in their sera developed painful peripheral neuropathies during treatment with synthetic nucleoside analogues such as Zidovudine (ZDV) or Didanosine (ddI), whereas patients that did not experience peripheral neuropathies during ZDV or ddI treatment had normal levels of L-acetylcarnitine [13].…”
Section: Hiv-associated Sensory Neuropathymentioning
confidence: 99%
“…After treatment with antiretroviral drugs, 10-30% of patients report signs of drug-associated peripheral neuropathies, such as a bilateral pain and burning dysesthesia in the lower extremities [49,37,35,36]. In a non-randomized clinical trial, Famularo and colleagues reported that HIV patients with lower levels of L-acetylcarnitine in their sera developed painful peripheral neuropathies during treatment with synthetic nucleoside analogues such as Zidovudine (ZDV) or Didanosine (ddI), whereas patients that did not experience peripheral neuropathies during ZDV or ddI treatment had normal levels of L-acetylcarnitine [13].…”
Section: Hiv-associated Sensory Neuropathymentioning
confidence: 99%
“…Since the time it was first introduced for the treatment of AIDS, ddC was causally connected with a dose-dependent, painful, sensorimotor axonal peripheral neuropathy (Berger et al, 1993;Blum et al, 1996;Dubinsky et al, 1989;Lewis and Dalakas, 1995;Moyle and Sadler, 1998). The neuropathy occurs in 34% of patients receiving ddC, and it is a limiting factor in the use of this drug in the treatment of AIDS (Dalakas, 2001;Dubinsky et al, 1989;Berger et al, 1993;Lewis and Dalakas, 1995;Blum et al, 1996;Moyle and Sadler, 1998).…”
mentioning
confidence: 99%
“…However, as the life expectancy of HIV-infected individuals increases, the prevalence of peripheral neuropathies in individuals with HIV likely is increasing (Sacktor, 2002). This problem is exacerbated by the neuropathy that results from HAART in addition to HIV infection-related neuropathy and neuropathy resulting from opportunistic infections (Hurst, 1999;Moyle and Sadler, 1998;Patel et al, 1989). The HAART-related neuropathies generally result from administration of antiretrovirals such as zalcitabine, didanosine, or stavudine (Simpson and Tagliati, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…eripheral neuropathy can result from the direct infection of neurons with human immunodeficiency virus (HIV), opportunistic infection of neurons because of generalized immunosuppression, and from highly active antiretroviral therapy (HAART) (Hurst, 1999;Moyle and Sadler, 1998). Furthermore, the increased life expectancy of HIV-infected individuals through HAART increases the prevalence of peripheral neuropathies (Sacktor, 2002).…”
Section: Introduction Pmentioning
confidence: 99%